Investigating Reef Contact Rates of Snorkel Visitors at Koh Sak, Pattaya on Guided and Non-guided Coral Reef Tours - Phillips, Wayne (Applied Environmental Research, 2018)
Recreational snorkelling is a popular activity at Koh Sak, Pattaya Bay and although most snorkel visitors to the island arrive by speedboat on guided tours, many visitors arrive on tours that do not provide a guide. Because there is widespread agreement that reef-based tourism negatively impacts coral reefs it is important to understand the potential role guides play in reducing visitor impacts. In this study 421 snorkelers (35 % of whom came on non-guided tours) were observed on the reef for a period of 10 minutes. The following information was recorded so that a per person reef-contact rate could be calculated: the snorkelers’ distance from their guide (if they had one), the number of people in their snorkelling group, and the number of contacts with the reef. There was no difference in contact rate between males (0.09 contacts min-1) and females (0.11 contacts min-1) nor was there any difference based on the group size (2-7 people). However, contact rates for snorkelers on tours with no guide (0.09 contacts min-1) and snorkelers far from their guide (0.08 contacts min-1) were significantly lower than visitors who snorkelled near their guide (0.18 contacts min-1; p < 0.001). The contact rate of guides (0.36 contacts min-1) was significantly greater than the snorkelers they were looking after (0.17 contacts min-1) in part due to the lack of knowledge and experience of snorkelers and guides alike. To reduce negative impacts to the coral reefs of Koh Sak guides need to change their destructive behaviour and improve their knowledge of reef biology and ecology.